Ethically designing research to inform multidimensional, rapidly evolving policy decisions: Lessons learned from the PROMISE HIV Perinatal Prevention Trial. (December 2021) - Shah, Seema K; London, Alex John; Mofenson, Lynne; Lavery, James V; John-Stewart, Grace; Flynn, Patricia; Theron, Gerhard; Bangdiwala, Shrikhant I; Moodley, Dhayendre; Chinula, Lameck; Fairlie, Lee; Sekoto, Tumalano; et al.
Research in rapidly evolving policy contexts can lead to the following ethical challenges for sponsors and researchers: the study's standard of care can become different than what patients outside the study receive, there may be political or other pressure to move ahead with unproven interventions, and new findings or revised policies may decrease the relevance of ongoing studies. These ethical challenges are considerable, but not unprecedented. In this article, we review the case of a multinational, randomized, controlled perinatal HIV prevention trial, the "PROMISE" (Promoting Maternal Infant Survival Everywhere) study. PROMISE compared the relative efficacy and safety of interventions to prevent mother to child transmission of HIV. The sponsor engaged an independent international ethics panel to address controversy about the study's standard of care and relevance as national and international guidelines changed. This ethics panel concluded that continuing the PROMISE trial as designed was ethically permissible because: (1) participants in all arms received interventions that were effective, and there was insufficient evidence about whether one intervention was more effective or safer than the other, and (2) data from PROMISE could be useful for a diverse range of stakeholders. In general, trials designed to inform rapidly evolving policy issues should develop mechanisms to revisit social value while recognizing that the value of research varies for diverse stakeholders with legitimate reasons to weigh evidence differently. We conclude by providing four reasons that trials may depart from the standard of care after a change in policy, while remaining ethically justifiable, and by suggesting how to improve existing trial oversight mechanisms to address evolving social value.